Macrophage IL-1β contributes to tumorigenesis through paracrine AIM2 inflammasome activation in the tumor microenvironment - Chew, Zhi Huan; Cui, Jianzhou; Sachaphibulkij, Karishma; Tan, Isabelle; Kar, Shreya; Koh, Kai Kiat; Singh, Kritika; Lim, Hong Meng; Lee, Soo Chin; Kumar, Alan Prem; Gasser, Stephan; Lim, Lina H. K. (Frontiers in Immunology, 2023)
Intracellular recognition of self and non-self -nucleic acids can result in the initiation of effective pro-inflammatory and anti-tumorigenic responses. We hypothesized that macrophages can be activated by tumor-derived nucleic acids to induce inflammasome activation in the tumor microenvironment. We show that tumor conditioned media (CM) can induce IL-1β production, indicative of inflammasome activation in primed macrophages. This could be partially dependent on caspase 1/11, AIM2 and NLRP3. IL-1β enhances tumor cell proliferation, migration and invasion while coculture of tumor cells with macrophages enhances the proliferation of tumor cells, which is AIM2 and caspase 1/11 dependent. Furthermore, we have identified that DNA-RNA hybrids could be the nucleic acid form which activates AIM2 inflammasome at a higher sensitivity as compared to dsDNA. Taken together, the tumor-secretome stimulates an innate immune pathway in macrophages which promotes paracrine cancer growth and may be a key tumorigenic pathway in cancer. Broader understanding on the mechanisms of nucleic acid recognition and interaction with innate immune signaling pathway will help us to better appreciate its potential application in diagnostic and therapeutic benefit in cancer.